Role of Surface Effects in the Vibrational Density of States and the Vibrational Entropy in Spin Crossover Nanomaterials: A Molecular Dynamics Investigation - Alaa Fahs; William Nicolazzi; Gábor Molnár; Azzedine Bousseksou (Magnetochemistry, 2021)
Size reduction effects on the lattice dynamics of spin crossover (SCO) thin films have been investigated through molecular dynamics (MD) simulations of the density of vibrational states. The proposed simple model structure and reduced force field allows us to obtain good orders of magnitude of the sound velocity in both spin states and takes into account the contribution of free surfaces in the vibrational properties of very thin films (below a thickness of 12 nm). The slab method issue from the field of surface physico-chemistry has been employed to extract surface thermodynamic quantities. In combination with the related slab-adapted method, the slab approach provides a powerful numerical tool to separate surface contributions from finite-size effects. Due to the relatively low stiffness of SCO materials, the lattice dynamics seems to be governed by surface instead of confinement effects. The size evolution of thermodynamic quantities is successfully reproduced, especially the increase of the vibrational entropy with the size reduction, in good agreement with experimental observations.